MOOC (MASSIVE OPEN ONLINE COURSE): RESPONDING EDUCATIONAL CHALLENGES IN THE FOURTH INDUSTRIAL REVOLUTION ERA - Mahmudah, Mahmudah (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
This article discusses the MOOC (Massive Open Online Course) platform for responding to educational challenges in the 4